Water Quality Monitoring Of Golden Arowana (Scleropages Formosus) At Ornamental Aquaculture Farm, Bukit Merah, Perak - Awalluddin, Nur Atiqah Ahmad (2013)
Water quality monitoring for Arowana is to investigate the required water quality that is suitable for the fish and hence encourage its breeding. The purpose is solely to preserve this Malaysian heritage species since Bukit Merah is the only place where Golden Arowana was found to be successfully bred. A number of 14 sampling points were selected in series from upstream at Bukit Merah reservoir and end up downstream at Sungai Kurau.